2012
DOI: 10.1097/ta.0b013e31821bf541
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Nrf2 exacerbated the damage after spinal cord injury in mice

Abstract: Genetic ablation of Nrf2 exacerbated the neurologic deficit and inflammation after SCI in mice. These findings raise the possibility that Nrf2 could be relevant in improving outcome after SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…While our work was in progress, two sets of researchers reported that SF treatment of rodents subjected to SCI leads to improvements in functional and anatomical recovery. 24,25 These studies are in full agreement with our findings that SF treatment after SCI improves hindlimb behavioral outcomes. Furthermore, increases in serotonergic axons caudal to the lesion site in injured SF-treated rats suggest a further protective role for SF administration after SCI.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…While our work was in progress, two sets of researchers reported that SF treatment of rodents subjected to SCI leads to improvements in functional and anatomical recovery. 24,25 These studies are in full agreement with our findings that SF treatment after SCI improves hindlimb behavioral outcomes. Furthermore, increases in serotonergic axons caudal to the lesion site in injured SF-treated rats suggest a further protective role for SF administration after SCI.…”
supporting
confidence: 90%
“…25 In our study SF treatment significantly increased expression of the quintessential Nrf2 markers NQO1 and HO-1 at 4 h after contusive SCI. The importance of the Nrf2 pathway in SFmediated protection against SCI has been established in Nrf2 knockout mice, 24,38 which showed increased edema and inflammation (IL-6 and IL-1b protein), and increased neuronal death in the injured spinal cord, and more severe hindlimb motor dysfunction with no improvements upon SF treatment. 24,38 In wildtype mice, acute treatment with SF leads to protective effects, including decreased edema and fewer dying neurons in the spinal cord 48 h after injury, and improved hindlimb motor function during the first week after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Mice having Nrf2 deficiency exhibit consistent impairment in locomotor functions after compression [95,98] and contusion SCI [97] . One of the main factors responsible for the diminished recovery of motor functions after SCI is demyelination, resulting from the delayed apoptotic death of oligodendrocytes [99] .…”
Section: Sci Induces Death Of Neuronal and Glial Cells As Well As Inmentioning
confidence: 99%
“…Importantly, patients with SCI have increased oxidative stress for at least one year after the initial injury [94] . 95,96] . Furthermore, utilizing a mouse contusion model we recently showed that the induction of Nrf2 is sustained, lasting at least 42 days, and forms a delayed peak at 7 days after injury [97] .…”
Section: Sci Induces Death Of Neuronal and Glial Cells As Well As Inmentioning
confidence: 99%
See 1 more Smart Citation